2019
DOI: 10.1097/apo.0000000000000250
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Insulin-Like Growth Factor-1 on Diabetic Retinopathy in Pubertal Age Patients With Type 1 Diabetes

Abstract: Purpose: The aims of this study were to correlate diabetic retinopathy (DR) changes with insulin-like growth factor 1 (IGF-1) levels in patients with type 1 diabetes of pubertal age group and to correlate the level of retinopathy with IGF-1 levels. Methods: This cross-sectional study was done over 2 years and involved patients with type 1 diabetes of age 8 to 25 years. Patients presenting to Ophthalmology OPD and inpatient department along with active recruitment from o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Hepatocytes secrete IGF1 upon stimulation with insulin and growth hormone (GH) (40). T1D patients with very low or undetectable levels of insulin also exhibit reduced plasma IGF1 levels (41). Reduced serum insulin and IGF1 concentrations in STZ induced T1D mice may trigger enhanced expression of IGF1 and IGF1R on CD8 + T cells upon cognate (tumor) antigen stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocytes secrete IGF1 upon stimulation with insulin and growth hormone (GH) (40). T1D patients with very low or undetectable levels of insulin also exhibit reduced plasma IGF1 levels (41). Reduced serum insulin and IGF1 concentrations in STZ induced T1D mice may trigger enhanced expression of IGF1 and IGF1R on CD8 + T cells upon cognate (tumor) antigen stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…DR very rarely develops before 10 years of age [30] and ISPAD guidelines suggest to start screening for DR from age 11 years [31] and also individuals aged between 10 to 24 year are defined as young people [32] are the reasons behind choosing this age range.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism underlying decreased retinal vessel density after insulin intensification in patients with type 2 diabetes mellitus is unclear. Studies have shown [ 37 39 ] that insulin-like growth factor (IGF-1) can affect the function of retinal endothelial progenitor cells under hypoxia and promote retinal angiogenesis, which plays a vital role in the occurrence and development of DR and causes EWDR.…”
Section: Discussionmentioning
confidence: 99%